LITERATURE REVIEW: SELF AWARENESS OF BADUY NONOMAN - Hakim, Ibrahim Al; Khairun, Deasy Yunika (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2021)
This article aims to describe the self-awareness of Baduy nonoman (adolescents). This article uses a literature review method. Literature is obtained from various articles. The analysis unit in this article is written documents about self-awareness research in the form of journal articles and research reports through an online journal database. "Self-awareness" and "nonoman-baduy" are used as keywords in the search for articles. The article is reviewed and analyzed to explain the self-awareness of Baduy nonoman. The results of the study indicate that the self-awareness of Baduy nonoman is the result of their view of life that is rooted in Sunda Wiwitan. This article contains a description of the career commitments of students in Baduy subculture.